Fostering inmates’ self-identity and communication via Drama in Education and puppetry An action research study at the Volos Youth Detention Centre - Vitsou, Magda; Magos, Kostas (Education & Theatre, 2023)
This postdoctoral research paper aims to shed light on the positive impact of implementing puppetry and Drama in Education (henceforth DiE) in correctional facilities, using a transformative perspective. The study examines whether incarcerated individuals experience changes in their attitudes, increased emotional strength, stronger interpersonal connections, enhanced teamwork, improved communication skills and greater self-awareness. Furthermore, the research emphasises a multifaceted approach that leverages puppet theatre and DiE techniques to address moral dilemmas. This approach has the potential to navigate ethical challenges that arise during imprisonment, facilitate smoother reintegration into society and effectively tackle issues such as discrimination, tensions and conflict resolution within correctional institutions.